Comparison of Intravoxel incoherent motion imaging and multiecho dynamic contrast‐based MRI in rectal cancer. Issue 4 (4th April 2019) - Bakke, Kine Mari; Grøvik, Endre; Meltzer, Sebastian; Negård, Anne; Holmedal, Stein Harald; Mikalsen, Lars Tore G.; Lyckander, Lars Gustav; Ree, Anne H.; Gjesdal, Kjell‐Inge; Redalen, Kathrine R.; Bjørnerud, Atle
Abstract : Background: Dynamic contrast‐based MRI and intravoxel incoherent motion imaging (IVIM) MRI are both methods showing promise as diagnostic and prognostic tools in rectal cancer. Both methods aim at measuring perfusion‐related parameters, but the relationship between them is unclear. Purpose: To investigate the relationship between perfusion‐ and permeability‐related parameters obtained by IVIM‐MRI, T1 ‐weighted dynamic contrast‐enhanced (DCE)‐MRI and T2 *‐weighted dynamic susceptibility contrast (DSC)‐MRI. Study Type: Prospective. Subjects: In all, 94 patients with histologically confirmed rectal cancer. Field Strength/Sequence: Subjects underwent pretreatment 1.5T clinical procedure MRI, and in addition a study‐specific diffusion‐weighted sequence (b = 0, 25, 50, 100, 500, 1000, 1300 s/mm 2 ) and a multiecho dynamic contrast‐based echo‐planer imaging sequence. Assessment: Median tumor values were obtained from IVIM (perfusion fraction [ f ], pseudodiffusion [ D* ], diffusion [ D ]), from the extended Tofts model applied to DCE data ( K trans, k ep, v p, v e ) and from model free deconvolution of DSC (blood flow [BF] and area under curve). A subgroup of the excised tumors underwent immunohistochemistry with quantification of microvessel density and vessel size. Statistical Test: Spearman's rank correlation test. Results: D* was correlated with BF (rs = 0.47, P < 0.001), and f was negatively correlated with k ep (rs = –0.31, P = 0.002). BF was correlated with K trans (rs = 0.29, P = 0.004), but this correlation varied extensively when separating tumors into groups of low (rs = 0.62, P < 0.001) and high (rs = –0.06, P = 0.68) BF . K trans was negatively correlated with vessel size (rs = –0.82, P = 0.004) in the subgroup of tumors with high BF . Data Conclusion: We found an association between D* from IVIM and BF estimated from DSC‐MRI. The relationship between IVIM and DCE‐MRI was less clear. Comparing parameters from DSC‐MRI and DCE‐MRI highlights the importance of the underlying biology for the interpretation of these parameters. Level of Evidence: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;50:1114–1124.